Acupuncture Treatment for Patients with Xuan Yun Syndrome with Kidney Yin Deficiency and Liver Hyperactivity at Griya Sehat Metta Tegal Alur, West Jakarta - Junet,; Wulandari, Mayang; Mahadini, Chantika; Amal, (Jurnal Indonesia Sosial Sains, 2026)
Vertigo or Xuan Yun is a vestibular disorder causing spinning sensations and significantly affecting quality of life. Pharmacological management may cause adverse effects; therefore, complementary therapy is required. This study aimed to analyze the effectiveness of acupuncture care in a patient diagnosed with Kidney Yin Deficiency and Liver Yang Rising syndrome. A single-case study design was applied to a 43-year-old female with chronic vertigo. Five therapy sessions were conducted. Evaluation used the Visual Analog Scale (VAS) and Dizziness Handicap Inventory (DHI). Results showed a decrease in VAS score from 7 to 0 and DHI score from 56 to 8. Clinical improvement was also observed in Wang, Wen, and Qie examinations. Acupuncture was effective in reducing vertigo intensity and improving functional activity through Qi regulation and Yin–Yang balance restoration.